Glucocorticoid-Induced Leucine Zipper Inhibits Interferon-Gamma Production in B Cells and Suppresses Colitis in Mice - Bruscoli, Stefano; Sorcini, Daniele; Flamini, Sara; Gagliardi, Andrea; Adamo, Francesco; Ronchetti, Simona; Migliorati, Graziella; Bereshchenko, Oxana; Riccardi, Carlo (Frontiers in Immunology, 2018)
Glucocorticoid-induced leucine zipper (GILZ) is transcriptionally up-regulated by glucocorticoids (GCs) and mediates many of the anti-inflammatory effects of GCs. Since B cell activity has been linked to cytokine production and modulation of inflammatory responses, we herein investigated the role of GILZ in B cells during colitis development. B cell-specific gilz knock-out (gilz B cKO) mice exhibited increased production of the pro-inflammatory cytokine IFN-γ in B cells, and consequently CD4+ T cell activation. Increased IFN-γ production in B cells was associated with enhanced transcriptional activity of the transcription factor Activator Protein 1 (AP1) on the IFN-γ promoter. Moreover, GILZ deficiency in B cells was linked to enhanced susceptibility to experimental colitis in mice, and this was reversed by administering GILZ protein. Interestingly, we observed increased production of IFN-γ in both B and T cells infiltrating the lamina propria of gilz B cKO mice. Together, these findings indicate that GILZ controls IFN-γ production in B cells, which also affects T cell activity, and increased production of IFN-γ by B and T cells in lamina propria is associated with predisposition to inflammatory colitis in mice.